REPRESENTATION OF GENERAL DIFFERENCES IN THE INTELLECTUAL NOVELS BY V. PETROV-DOMONTOVYCH - Tetyana I. Virchenko (Вісник університету ім. А. Нобеля. Серія Філологічні науки)
The study focuses in the representation of generational differences on the material of V. PetrovDomontovych’s novels. Attention to generational studies is due to their significant potential, which lies in forecasting the development of society, understanding of worldviews, therapeutic functions, and more. Research attention was focused on the artistic realization of the factors that create generations, the delineation of their values, social positions, worldviews, and the peculiarities of the intersection of generations. This has been the purpose of the study. The implementation of the study required the definition of the meaning of “generation”. It is based on the definition of A. Mausyak, M. Svetlitsky, formulated in the work in “Category of generation in modern socio-cultural research”: “A group of peers characterized by a certain worldview and specific ideas, values, positions, norms, patterns of social positions, as well as the similarity of historical experience or common living conditions…” In the novel “Without Soil” the value and monument, through the prism of which generational differences will be understood, was the Varangian Church, built by Linnik. Linnyk, Rostyslav Mykhailovych, and Hulya are related to one art form and best reflect the evolutionary changes that are taking place; illustrate intergenerational communication. Linnyk, a representative of the “senior” generation, is an incredulous, always gloomy recluse. Dedication to work, perseverance in the fight against everyday life, form Linnik’s understanding of the mission of art: to appeal to the mind of the recipient. Rostislav Mikhailovich has an understanding of the peculiarities of the thinking of people in the middle of the 20th century – the ability to think in contradictions, to distinguish the differences of the era. The worldview of the “younger” generation is devoid of depth, marked by the loss of soil, the devaluation of the role of memory. V. Petrov-Domontovych emphasizes the different attitude of the representatives of the generations to the understanding of the essence of the “movement”. It is important for the older generation to understand the connection between the generations, to express the cause-and-effect relations, to preserve the memory. In contrast to Linnyk, Rostyslav Mykhailovych does not accept the world of values that tries to dominate society, so he chooses the path of “internal emigration”, which serves as a means of resisting the influence of other individuals. The analysis allows us to identify several motives for internal emigration: fatigue from everyday life, lack of connections in the community, the conflict between the awareness of their origin and the present, the instinct of self-preservation. All the motives that cause internal emigration are a necessity, just as internal emigration itself is necessary for the sake of the ability to feel, see, think, express one’s thoughts; for the sake of being able to be oneself, for the sake of self-preservation of individuality